MicroRNAs in Cancer: Small Molecules, Big Chances - Abba, Mohammed; Mudduluru, Giridhar; Allgayer, Heike (Anti-Cancer Agents in Medicinal Chemistry, 2012)
MicroRNAs have come to represent a significant mechanism of post transcriptional gene regulation affecting processes as varied as cellular differentiation, proliferation, metabolism, apoptosis, and cancer. As more miRNAs are unravelled and their roles dissected, it has become evident that the involvement of these molecules in cancer is much more extensive than initially thought. Several miRNA expression analyses in both haematological malignancies and solid tumors have shown that, aside significant differences in expression between tumor and normal states, distinct tumor specific miRNA signatures exist. Additionally, the ability of miRNAs to mediate both oncogenic and tumor suppressor functions further broadens their functional significance. In recent years, efforts have intensified to utilize miRNAs therapeutically, especially in the context of oncomirs. As far as the impact and the success of this approach are concerned, it is still early days, but the potential is enormous. This review focuses on the important miRNAs that have been found to impact the tumorigenic process, how far we have come in terms of utilizing these molecules for therapy and the outlook for the near future.
Keywords: Paralogous